Personal Growth Initiative and Self-Regulated Learning in Students with Low Intelligence Potential (Sains Humanika, 2021)
Students with low intelligence potential, have limitations in academic matters. Unlike students with average intelligence, students with low intelligence will find difficulties in completing their academic tasks. Frequently, when their intelligence potentials have not been identified and are included in a regular class, they have to meet the same demands with other students who have normal/average intelligence. Therefore, they struggle to complete the given academic tasks. Their efforts to manage thoughts, feelings and behavior to achieve goals are called Self Regulated Learning (SRL). This study aims to determine the relationship of Personal Growth Initiative (PGI) and Self Regulated Learning in students with low intelligence potential. The research method used is quantitative correlational. The data collection tool used is the PGI and SRL Likert scale; the results of the filling scale are analyzed by product moment correlation statistical techniques. The results show a positive relationship between PGI and SRL (r = 0.677, sig. 0.032) with a contribution of 45.8%. The implication that can be drawn from this research is that it provides proper psychological treatment to students with low intelligence potential so that they can stay motivated in learning process.
Keywords: Personal Growth Inisiative, Self Regulated Learning, Low Intelligence.